PENGARUH KARAKTER BAJA S45C PADA PROSES QUENCH – TEMPER - Veny Selviyanty (Jurnal Teknik Industri Terintegrasi, 2021)
S45C steel is widely used in the industrial world, one of which is machining construction. problems that often occur in the engine components are worn out, broken, cracks that can be caused due to overload (over load), so the construction design is not as expected. With S45C steel is widely used in the industrial world, one of which is machining construction. problems that often occur in the engine components are worn out, broken, cracks that can be caused due to overload (over load), so the construction design is not as expected. With the above problems, it is desirable for a construction material that is hard and also resilient to prevent damage. Then in order to obtain good results, the components of the machines are then given heat treatment such as hardening which aims to improve the properties of the metal.From the results of testing the hardness obtained the highest value on the quenching test. In impact testing for raw material specimens with an average value of 0.811 J / mm2, in the quenching pesimen the average value was 0.483 J / mm2 and in the tempering tempering was 1.282 J / mm2. From the results of the impact testing, the highest values were found in the tempering templates. The microstructure of JIS S45C steel after heating undergoes a change in microstructure wherein the specimens of tempering ferrite and pearlite structures get smaller and spread, this is due to slow cooling, in contrast to specimens quenching because heat treatment is carried out through temperature and rapid cooling with water media so that the structure does not have enough time to diffuse.